Farmers’ preferences for the next generation of maize hybrids: application of product concept testing in Kenya and Uganda - Donovan, Jason; Rutsaert, Pieter; Mawia, Harriet; De Sousa, Kaue; Van Etten, Jacob (Cambridge University Press, 2025)
Step-change innovation in seed product design by public sector crop breeding has led to major contributions to global food security. The literature, however, provides few insights on how to identify forward-looking innovation opportunities. Inspired by discussions in the product innovation literature, this article describes our application of product concept testing in the context of hybrid maize in Uganda and Kenya. We identified the following eight maize seed product concepts based on interactions with seed companies, crop breeders, and farmers: ‘Resilience’, ‘Drought escape’, ‘Food and fodder’, ‘Home use’, ‘Green maize’, ‘Livestock feed’, ‘Intercropping’, and ‘Family nutrition’. These were described and presented to 2400 farmers using videos, where each farmer saw three concept-presentation videos. Farmers were most likely to have selected the resilience (Kenya and Uganda), drought escape (Uganda), and intercropping (Kenya) concepts. Farmers showed mixed interest in other concepts, such as home use and food and fodder, suggesting that investments in product production and promotion would be required in addition to investments in breeding. These results provide new entry points for conversations among transdisciplinary teams at regional and national levels on the current and future opportunities for crop breeding to respond to farmers’ requirements for new seed products.